2011
DOI: 10.1097/inf.0b013e3181ed2af3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Children Receiving Antiretroviral Treatment in Rural South Africa

Abstract: ART provides significant benefits for children in this rural African setting, but the finding that a large proportion of children had virologic failure and developed major drug-resistance mutations on first-line ART is worrying. Causes of failure need to be analyzed and effective prevention strategies are needed. Because of the lack of a correlation between immunologic and virologic failure, treatment failure generally stays unnoticed in settings where HIV-RNA testing is not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
47
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 31 publications
9
47
4
Order By: Relevance
“…Unsuppressed viremia leads to accumulation of resistance mutations and patients monitored by clinical or immunologic criteria tend to have increased durations of unsuppressed viremia compared to those monitored with viral load [5]. Despite this limitation, a majority of adults in resource-limited settings have attained virologic suppression on second-line regimens, even in the context of clinical or immunologically driven monitoring strategies [6],[7].…”
Section: Introductionmentioning
confidence: 99%
“…Unsuppressed viremia leads to accumulation of resistance mutations and patients monitored by clinical or immunologic criteria tend to have increased durations of unsuppressed viremia compared to those monitored with viral load [5]. Despite this limitation, a majority of adults in resource-limited settings have attained virologic suppression on second-line regimens, even in the context of clinical or immunologically driven monitoring strategies [6],[7].…”
Section: Introductionmentioning
confidence: 99%
“…In [11] As evidence mounts for successful initiation of paediatric ART care in rural and urban community-based PHC clinics, [13][14][15][16][17][18] the need to evaluate paediatric down-referral outcomes remains. A systematic review of decentralised HIV care (including three studies with paediatric data) demonstrated comparable outcomes, with similar or reduced patient attrition and death at 12 months.…”
mentioning
confidence: 99%
“…A recent retrospective study implemented in another rural area of South Africa found similar rates (38%) of virological failure (median duration since beginning HAART of 31 months) [13].…”
Section: Discussionmentioning
confidence: 84%
“…Between 2005 and 2014, children treated with HAART increased from 71.500 to 824.000 [11] but long-term (>3 years) virological and immunological data collected in Sub-Saharan Africa are scarce [12][13][14][15][16]. Children are at risk to develop treatment failure due to inappropriate antiretroviral formulations, adherence difficulties, drug toxicity or development of resistance [17].…”
Section: Introductionmentioning
confidence: 99%